2017
DOI: 10.2140/ant.2017.11.39
|View full text |Cite
|
Sign up to set email alerts
|

Split abelian surfaces over finite fields and reductions of genus-2 curves

Abstract: ABSTRACT. For prime powers q, let split(q) denote the probability that a randomly-chosen principallypolarized abelian surface over the finite field F q is not simple. We show that there are positive constants c 1 and c 2 such that for all q,and we obtain better estimates under the assumption of the generalized Riemann hypothesis. If A is a principally-polarized abelian surface over a number field K, let π split (A/K, z) denote the number of prime ideals p of K of norm at most z such that A has good reduction a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Genesis of this project. We noticed this discrepancy while attempting to obtain numerical data in support of some earlier work [1]. Moreover, we found that one of us invoked an erroneous formula in a separate project [63] (see Section 5.2).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Genesis of this project. We noticed this discrepancy while attempting to obtain numerical data in support of some earlier work [1]. Moreover, we found that one of us invoked an erroneous formula in a separate project [63] (see Section 5.2).…”
supporting
confidence: 65%
“…One is given a further opportunity to make a "sign error" when one chooses bases for these vector spaces and then decides whether the semilinear operator acts on the right or on the left. 1 Given these multiple opportunities for mistake, it is hardly surprising that there are occasional misstatements in the literature.…”
Section: Prologuementioning
confidence: 99%
“…One can give a heuristic justification for our theorem as follows. Following results of Achter and Howe in [AH17], the number of non-simple principally polarized abelian surfaces over F q n is roughly q n(5/2+o(1)) , and the number of non-simple isogeny classes is roughly q n(1+o(1)) . Similarly, the total number of isogeny classes in A 2 is roughly q n(3/2+o(1)) .…”
mentioning
confidence: 61%
“…Proof of Proposition 6.14. From Lemma 6.13 (1), the curves in Orbit 1 for Z 1 and Z 2 are isogenous to one another. From Lemma 6.13(3), the curves in Orbits 2A and 2B for Z 1 are isogenous to the first pairs of Orbits 4A and 4B for Z 2 , respectively, and from Lemma 6.13 (5) applied to (4), the curves in Orbits 2A and 2B for Z 2 are isogenous to the second pairs of Orbits 4A and 4B for Z 1 , respectively.…”
Section: Description Of the Familiesmentioning
confidence: 94%